Autoimmune response to PARP and BRCA1/BRCA2 in cancer - Zhu, Qing (Oncotarget, 2015)
PURPOSE: To determine the role of autoantibodies to PARP1 and BRCA1/BRCA2 which were involved in the synthetic lethal interaction in cancer. METHODS: Enzyme-Linked Immunosorbent Assay (ELISA) was used to detect autoantibodies to PARP1 and BRCA1/BRCA2 in 618 serum samples including 131 from breast cancer, 94 from lung cancer, 34 from ovarian cancer, 107 from prostate cancer, 76 from liver cancer, 41 from pancreatic cancer and 135 from normal individuals. The positive sera with ELISA were confirmed by Western blot. Immunohistochemistry was used to examine the expression of PARP1 and BRCA1/BRCA2 in breast cancer. RESULTS: Autoantibody frequency to PARP1, BRCA1, and BRCA2 in cancer varied from 0% to 50%. When the sera from cancer patients were tested for the presence of autoantibodies to PARP1 and BRCA1/BRCA2, the autoantibody responses slightly decreased and the positive autoantibody reactions varied from 0% to 50.0%. This was significantly higher autoantibody responses to PARP1 and BRCA1/BRCA2 (especially to PARP1 and BRCA1) in ovarian cancer and breast cancer compared to normal control sera (P < 0.001 and P < 0.01). Immunohistochemistry indicated that Pathology Grade at diagnosis to PARP1 expression in breast cancer was different (P < 0.05). CONCLUSIONS: Different cancers have different profiles of autoantibodies. The autoantibodies to proteins involving the synthetic lethal interactions would be novel serological biomarker in some selective cancers.